Proliferative and anti-proliferative effects of thymosin α1 on cells are associated with manipulation of cellular ROS levels - Qin, Yong; Chen, Fu-Ding; Zhou, Liang; Gong, Xing-Guo; Han, Qi-Feng (Chemico-biological interactions, 2009)
Reactive oxygen species (ROS) are constantly generated and eliminated in the biological system and play important roles in a variety of physiological and pathological processes. Previous studies indicate that modulation of cellular ROS affects cell proliferation. Thymosin alpha 1 (Tα1) is a naturally occurring thymic peptide and has previously been shown to be a potential therapy for some immunodeficiencies, malignancies, and infections. However, few reports have focused on manipulation of cellular ROS level effects of Tα1. In this study, the Tα1-treated leukomonocytes, which were isolated from mice spleens, exhibited a higher ROS level and a lower reduced glutathione (GSH) level; however, HepG2 cells treated with Tα1 exhibited lower ROS level and higher GSH level. In addition, after treatment with Tα1, the population of leukomonocytes in the G 2 phase increased, resulting in a slight increase in viability. However, in Tα1-treated HepG2 cells, the cell cycle was delayed in the G 1 phase, thereby inhibiting tumor cell proliferation; in addition, dephosphorylation of the serine/threonine kinase Akt was detected. In conclusion, we show that Tα1 has potent anti-proliferative activity against malignant human hepatoma cells and proliferative activity against leukomonocytes associated with manipulation of oxidative stress levels which indicates the potential of Tα1 as an antitumor drug.